Solomon Islands : Workforce Development - World Bank (2015)
Solomon Islands has undertaken a comprehensive assessment of the strength of its workforce development (WfD) policies and institutions to support these initiatives and enhance evidence based dialogue on their implementation. This assessment has been based on the World Bank s Systems Approach for Better Education Results (SABER) systems benchmarking initiative, under which a suite of analytical tools have been developed for important education subsectors, including WfD. Both the process of carrying out the SABER WfD assessment and this report are intended to strengthen the existing deliberative processes on the major system reforms. The tool is based on an analytical framework that identifies three functional dimensions of WfD policies and institutions: (1) Strategic framework, which refers to the praxis of high level advocacy, partnership, and coordination, typically across traditional sectoral boundaries, in relation to the objective of aligning WfD in critical areas to priorities for national development; (2) System Oversight, which refers to the arrangements governing funding, quality assurance, and learning pathways that shape the incentives and information signals affecting the choices of individuals, employers, training providers, and other stakeholders; and(3) Service Delivery, which refers to the diversity, organization, and management of training provision, both state and non-state, that deliver results on the ground by enabling individuals to acquire market and job relevant skills.